log (5x-1) - log (x-2) = log 3

First we will simplify the equation:

We know that:

log a = log b = log a/b

==> log (5x-1)/(x-2) = log 3

Also, we know that:

if log a = log b ==> a = b

==> (5x-1) /(x-2) = 3

Now multiply by (x-2):

==> (5x-1) = 3(x-2)

==> 5x-1 = 3x - 6

Combine like terms:

==> 5x-3x = -6 + 1

==> 2x = -5

**==. X= -5/2**

**But the function is not defined when x= -5/2 **

**==> There is no solution.**

## We’ll help your grades soar

Start your 48-hour free trial and unlock all the summaries, Q&A, and analyses you need to get better grades now.

- 30,000+ book summaries
- 20% study tools discount
- Ad-free content
- PDF downloads
- 300,000+ answers
- 5-star customer support

Already a member? Log in here.

Are you a teacher? Sign up now